Surgical options in the treatment of endobronchial carcinoid tumor - Nawaf AlKharashi; Mohammed Al-Namshan; Jaber AlShammari; Mutaz Gieballa; Saud AlJadaan; Stanley Crankson (Elsevier, 2018)
Endobronchial carcinoid tumors (ECT) are the most common pulmonary neuroendocrine tumor in the pediatric population. We report two cases of ECT in children who presented with recurrent pneumonia and bronchial asthma-like symptoms. Rigid bronchoscopy revealed an endobronchial mass with biopsy confirming the diagnosis. Both children underwent surgical resection with an uneventful post-operative course. Neither of children required adjuvant chemotherapy nor radiotherapy and with a mean of follow-up of 8 years with no recurrence. Physicians should be aware that children with recurrent pneumonia and asthma-like symptoms may have ECT. Appropriate investigations including CT scan, bronchoscopy, and biopsy would ensure early diagnosis and surgery.